Correlation of Memory Ability with Learning Outcomes Students at Elementary School - Izza, Ni'matul; Zanah, Wardah Tul; R, Putri Utami; AM, Ahmad Giri (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to examine the correlation of students' memory skills to the mathematics learning outcomes of fourth grade students at SDN Jurumudi 4, Tangerang city. The method used is quantitative correlation. The data analysis technique uses a significance of 0.05 with a prerequisite test consisting of a normality test, linearity test, hypothesis testing (product moment person correlation and correlation coefficient significance test with the t test). The results of this study: (1) students' memory skills through descriptive statistical analysis found that there were 32 students in grade IV C at SDN Jurumudi 4 Tangerang city with an average memory score of 81.09 in the high category. (2) The learning outcomes of students in class IV C at SDN Jurumudi 4 Tangerang city in learning mathematics about fractional material equal to the number of students as many as 32 people with an average score of 76.31 in the high category. (3) The results of hypothesis testing through inferential statistics show that there is a correlation between students' memory skills and the mathematics learning outcomes of fourth-grade students at SDN Jurumudi 4, Tangerang City, with a correlation coefficient (r) of 0.429 and sig.0.014. It can be seen from the table of the level of correlation and the strength of the relationship. between the two variables is at the magnitude of 0.40-0.599 indicating that there is a moderate or sufficient correlation. Furthermore, to test the hypothesis using the correlation coefficient significance test with the t test and the results obtained are tcount > ttable (2.601 > 2.042) the hypothesis is accepted.